Optimization of an Analytical Method for Determination of Pyrene in Smoked Meat Products - Ince, Muharrem; Ince, Olcay Kaplan; Yaman, Mehmet (Springer, 2017)
In the present study, an analytical method was optimized for determination of pyrene by solid-phase extraction in Turkish foodstuffs including chicken and grilled meat samples. In accordance with this purpose, all of the parameters that may affect the signal of pyrene during analysis processes were optimized using high-performance liquid chromatography-mass spectrometry system. The optimized parameters for column temperature, injection volume, mobile-phase flow rate, and fragmentor potential were found to be 45 degrees C, 60 mu L, 0.6 mL min(-1), and 130 V, respectively. The optimized high-performance liquid chromatography-mass spectrometry method was applied for the determination and evaluation of pyrene in food samples that include chicken and grilled meat. The pyrene amount in meat samples was obtained in the range from 2.3 to 4.4 mu g kg(-1) for the normal grilled meat and chicken samples and from 12 to 135 mu g kg(-1) for exceedingly grilled samples. The results show that the concentration of pyrene is significantly dependent on the type of meat sample and cooking source. The limit of detection and quantitation was found to be 0.5 mu g L-1 and 1.53 mu g L-1, respectively.
Keywords: Pyrene; Solid-phase extraction; High-performance liquid chromatography-mass spectrometry; Food; Grilled meat; Chicken